LINGUO-CULTURAL STUDY OF LEXICO-SEMANTIC GROUPS "CLOTHING" - Nygmanova D.K, (Academic Journal of Physical and Chemical Sciences, 2019)
The author conducted a survey study of lingua-cultural studies in the framework of a new direction, both scientific and for the purpose of the Internet communication field, by means of a comparative method, that is, it is devoted to building and analyzing the lexico-semantic field "Clothes" in Russian and English. The relevance of the research topic in the specifics of this vocabulary, since the analysis of its semantic aspect requires constant concentration to extra-linguistic reality, as well as to ethnographic factors. However, the study of the names of "clothing" as a community of structure, caused the need to take into account the changes occurring as a result of the transformation of economic and socio-political living conditions. In general, the picture of the world has undergone significant changes in the way new sectors have appeared - these are astronautics, the latest technologies, computer equipment, innovative projects, genetic engineering and more. Accordingly, a new sector in human activity automatically fixes attention on the lexical field.